Redox Characterization of Functioning Skeletal Muscle - Zuo, Li; Pannell, Benjamin K. (Frontiers in Physiology, 2015)
Skeletal muscle physiology is influenced by the presence of chemically reactive molecules such as reactive oxygen species (ROS). These molecules regulate multiple redox-sensitive signaling pathways that play a critical role in cellular processes including gene expression and protein modification. While ROS have gained much attention for their harmful effects in muscle fatigue and dysfunction, research has also shown ROS to facilitate muscle adaptation after stressors such as physical exercise. This manuscript aims to provide a comprehensive review of the current understanding of redox signaling in skeletal muscle. ROS-induced oxidative stress and its role in the aging process are discussed. Mitochondria have been shown to generate large amounts of ROS during muscular contractions, and thus are susceptible to oxidative stress. ROS can modify proteins located in the mitochondrial membrane leading to cell death and osmotic swelling. ROS also contribute to the necrosis and inflammation of muscle fibers that is associated with muscular diseases including Duchenne muscular dystrophy (DMD). It is imperative that future research continues to investigate the exact role of ROS in normal skeletal muscle function as well as muscular dysfunction and disease.